2008
DOI: 10.1016/j.vetimm.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Report of the 3rd Havemeyer workshop on allergic diseases of the Horse, Hólar, Iceland, June 2007

Abstract: Allergic diseases occur in most mammals, although some species such as humans, dogs and horses seem to be more prone to develop allergies than others. In horses, insect bite hypersensitivity (IBH), an allergic dermatitis caused by bites of midges, and recurrent airway obstruction (RAO), a hyperreactivity to stable born dust and allergens, are the two most prevalent allergic diseases. Allergic diseases involve the interaction of three major factors: (i) genetic constitution, (ii) exposure to allergens, and (iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 55 publications
0
36
0
1
Order By: Relevance
“…Hypersensitivity disorders are important in horses, with recurrent airway obstruction (RAO), insect bite hypersensitivity (IBH), and urticaria (URT) among the most frequently observed 1, 2, 3, 4, 5, 6. In other species, including humans, dogs, and cats, a combined occurrence of multiple hypersensitivities (MHS) affecting different organ systems has been described.…”
mentioning
confidence: 99%
“…Hypersensitivity disorders are important in horses, with recurrent airway obstruction (RAO), insect bite hypersensitivity (IBH), and urticaria (URT) among the most frequently observed 1, 2, 3, 4, 5, 6. In other species, including humans, dogs, and cats, a combined occurrence of multiple hypersensitivities (MHS) affecting different organ systems has been described.…”
mentioning
confidence: 99%
“…The absence of research standardization was correctly pointed out at the 3 rd Havemeyer workshop on allergic diseases where it was reported that "... no accepted recommendations exist for standardized exposure protocols and sampling time in experimental studies of RAO...", making comparison between studies difficult (Marti et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, to date, no accepted recommendations exist for standardized exposure protocols and sampling times in experimental studies of RAO (Marti et al 2007).…”
mentioning
confidence: 99%
“…However, although the immunological aspects of RAO have been extensively studied, the precise sequence of events is still not well understood. Moreover, the involvement of an IgE-mediated mechanism in the pathogenesis of RAO-affected horses remains unclear and is still controversial (Marti et al 2008;Wagner 2009). Wagner (2009) suggested that more recent studies did not confirm an IgE-mediated pathogenesis of RAO.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of IgE-mediated reactions in RAO remains unclear (Marti et al 2008;Tahon et al 2009;Wagner 2009). Today, various techniques are available to detect soluble IgE and the sensitization of mast cell or basophils with IgE horses (Wagner 2009).…”
Section: Introductionmentioning
confidence: 99%